Cytomegalovirus disrupts Lamin A/C to control microtubule-mediated nuclear movement and cell migration - Jamil Mahmud; Ipsita Nandi; Dean J. Procter; Derek Walsh (Proceedings of the National Academy of Sciences, 2025)
Human cytomegalovirus (HCMV) disrupts the inner nuclear Lamin A/C meshwork to facilitate virion egress. Here, we show that targeting Lamin A/C also plays a previously unrecognized role in HCMV-induced rewiring of cytoskeletal connections that control nuclear movement and cell migration at later stages of infection. Specifically, HCMV was found to employ distinct strategies to downregulate Lamin A/C and SUN2, which together regulate linker of nucleoskeleton and cytoskeleton (LINC) complexes that most often connect the nuclear membrane with cytoplasmic actin filaments. Unexpectedly, inhibition of the viral kinase, pUL97, or expression of nonphosphorylatable mutants of Lamin A/C failed to restore SUN2 expression or significant actin filament assembly. Moreover, exogenous reexpression of SUN2 also failed to restore actin filaments. Instead, restoration of SUN2 or Lamin A/C expression impaired the formation of acetylated microtubules in infected cells. Furthermore, inhibition of pUL97, expression of Lamin A/C mutants or depletion of the tubulin acetyl transferase, ATAT1, all impaired HCMV-induced nuclear movement and cell migration. Our findings reveal that HCMV uses multiple strategies to selectively downregulate Lamin A/C and SUN2 in order to prevent these proteins from interfering with the formation of acetylated microtubules that mediate nuclear movement and cell migration, revealing additional roles for Lamin A/C remodeling during infection and insights into how cells control cytoskeletal interactions with the nucleus.